Nearest neighbour queries on commercial databases - Lin, Xinzhen. (2012)
When you are in need of cash now, how can you quickly find the two nearest ATMs around you that are within one km? This can also be thought of as a k-nearest neighbour (KNN) problem. To help solving the problem, the objective of the project is to develop an application that allows users to search for a number of locations of a particular place type that are nearest to a given point on the map.